Pengaruh Agency Cost Terhadap Nilai Perusahaan Dengan Transparansi Informasi Sebagai Variabel Moderasi: Kata Kunci: Agency Cost, Transparansi Informasi, Nilai Perusahaan - Dewi Kusuma Wardani; Wahyu Tri Susilowati (Universitas Kristen Maranatha, 2020)
This study aims to test the effect agency costs towards company value with information transparency as a moderating variables. This sample used in this study is a manufacturing. This sample used is a manufacturing companies during the year 2013-2017, based on the method of purposive sampling obtained 58 manufacturing companies. This research used simple regression analysis and the test value of absolute difference. The results of the study indicate that agency cost has a positive effect on firm value. Information transparency can not moderate influence of agency cost to firm value.